Evaluation of preventive effects of interferon inducer against acute respiratory viral infections in young people - E. P. Tikhonova; T. Yu. Kuzmina; Yu. S. Kalinina (Лечащий Врач)
The results of observational non-interventional prospective study of application of kagocel for prevention of ARVI and influenza during epidemic rise of morbidity among young people were presented. During epidemic rise of morbidity in 2018 in young people who didn’t receive any drugs for the prevention of ARVI and influenza, the incidence rate of ARVI or influenza was high (40%). Against the background of the 28-day course of preventive kagocel administration, the incidence of ARVI or influenza was only 16%. The index of the preventive effectiveness during the study was: (I) = 40%/16% = 2,5.